Reactive oxygen species-responsive HET0016 prodrug-loaded liposomes attenuate neuroinflammation and improve neurological deficit in a rat model of juvenile traumatic brain injury - Qin, Jun; Chen, Xiaoli; Wang, Rui; Tian, Zedan; Li, Yang; Shu, Shiyu (Frontiers in Neuroscience, 2023)
The arachidonic acid pathway metabolite 20-hydroxyeicosatetraenoic acid (20-HETE) contributes to ischemia/reperfusion brain injury. Inhibition of 20-HETE formation can protect the developing brain from global ischemia. In previous studies, we have found that treatment with the 20-HETE synthesis inhibitor N-hydroxy-N-4-butyl-2-methylphenylformamidine (HET0016) can protect the immature brain from traumatic brain injury (TBI), but its hydrophobic nature limits its full potential. We designed a reactive oxygen species-responsive HET0016 prodrug, which consists of a thioketal link between HET0016 and stearyl alcohol (HET-TK-SA), and used the nanoprodrug strategy to successfully synthesize liposomes (HPLs) to facilitate the application of HET0016 in protection from TBI. HPLs demonstrated spherical shape, size of about 127.8 nm, a zeta potential of -28.8 mv, a narrow particle size distribution and good stability. Male rats at postnatal day 16–17 underwent controlled cortical impact (CCI) followed by intravenous injection with vehicle or HET0016 (1 mg/kg, 2 h post-injury, once/day for three days). The results of the in vivo demonstrated that HPLs has good biosafety and can pass through the blood-brain barrier. Not only that compared with HET0016, HPLs better-inhibited inflammation and improved neuronal degeneration, which further led to lesion volume reduction, upgraded behavioral task performance, and ameliorated the degree of TBI impairment. Our results demonstrated HPLs could be a new strategy for juvenile TBI therapy.